Why Financial Behavior Differs: The Roles of Fintech Literacy, Social Comparison, and Anxiety - Yuli Rahmini Suci; Roswiyanti Roswiyanti; Andi Widiawati; Lilik Handayani; Johannes Baptista Halik (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the effects of perceived fintech literacy and social comparison orientation on financial behavior among productive-age adults in Indonesia, with financial anxiety as a mediating mechanism. Design/Methodology/Approach – A quantitative explanatory study was conducted using a cross-sectional survey of 210 productive-age fintech users in Indonesia. Respondents were selected through purposive sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings – Perceived fintech literacy positively affects both financial behavior and financial anxiety. Social comparison orientation significantly increases financial anxiety but has no direct effect on financial behavior. Financial anxiety positively influences financial behavior, partially mediating the relationship between fintech literacy and financial behavior, and fully mediating the relationship between social comparison orientation and financial behavior. Originality/Value – This study extends the behavioral finance literature by identifying financial anxiety as a key mechanism linking fintech literacy and social comparison orientation to financial behavior. The findings emphasize the importance of integrating cognitive, social, and psychological factors in financial education and policy to promote responsible financial decision-making.